Business Roadmap Model: A Review of Research - Finnah Fourqoniah; Riyan Danu Setiawan; Muhammad Fikry Aransyah (Universitas Diponegoro, 2021)
In doing business, business actors must understand the importance of a business model in entrepreneurship; a business strategy is needed. There are several business models, but the one most often used by business actors is the Business Model Canvas or what we usually know (BMC). According to several studies, the Business Model Canvas is a business model that can still be developed into a more detailed business model and better mapping. Then from the Business Model Canvas, a new business model was developed, namely the Business Road Map, to win the market competition. Business Road Map is a pattern or Business Mapping Method to build a business model/business plan capable of creating growth over time.